Association of high disease activity and serum IL-6 levels with the incidence of inflammatory major organ events in Behçet disease: a prospective registry study - Hirahara, Lisa; Kirino, Yohei; Soejima, Yutaro; Iizuka, Yuki; Yoshimi, Ryusuke; Fujieda, Yuichiro; Atsumi, Tatsuya; Tono, Toshihiro; Kobayashi, Daisuke; Meguro, Akira; Takeuchi, Masaki; Sakamaki, Kentaro; et al. (Frontiers in Immunology, 2024)
Little is known about the relationship between the disease activity of Behçet disease (BD) and the incidence of inflammatory major organ events.In this prospective registry study, we investigated the association between the Behçet Disease Current Activity Form (BDCAF) and incidence of inflammatory major organ events, defined as the inflammation of the ocular, central nervous, intestinal, and vascular systems in BD.We enrolled participants from Japanese multicenter prospective cohorts. The BDCAF was evaluated annually. BD-related symptoms, including inflammatory major organ events, were monitored. The association between BDCAF and inflammatory major organ events was analyzed by time-to-event analysis. An unsupervised clustering of the participants' BDCAF, therapeutic agents, and multiple serum cytokines was also performed to examine their association with inflammatory major organ events. Results: A total of 260 patients were included. The patients had a median BDCAF score of 2 [Interquartile range, 1-3] at the enrolment and remained disease active at 1-and 2-year follow-ups, indicating residual disease activity in BD. Patients with a BDCAF score of 0 had a longer inflammatory major organ event-free survival at 52 weeks than those with a score of 1 or higher (p=2.2 x 10 -4 ). Clustering analysis revealed that patients who did not achieve remission despite treatment with tumor necrosis factor inhibitors had high serum inflammatory cytokine levels and incidences of inflammatory major organ events. Among the elevated cytokines, IL-6 was associated with inflammatory major organ events.This study suggests that treatment strategies targeting overall disease activity and monitoring residual serum IL-6 may help prevent inflammatory major organ events in BD.